Strengthening Cultural Identity in Empowering the Badui Community: A Case Study of Social Facilitation - Pratiwi, Esti Utami; Asnawati, Yeti; Fauzi, Yudiansyah; Pari, Riki Aldi; Ripai, Rizki; Sidik, Fazar; Aditia, Rifki; Meilany, Zubeida; Sofiana, Nana (EQUATOR SINAR AKADEMIA, 2024)
The preservation and promotion of cultural heritage are crucial for fostering social cohesion and identity within communities, particularly among indigenous groups facing the pressures of modernization. This study examines the role of cultural identity strengthening in empowering the Badui community, a traditional indigenous group in Indonesia. Through a detailed case study of social facilitation efforts, the research explores the strategies employed, outcomes achieved, and lessons learned, contributing to a broader understanding of the interplay between cultural identity and community development.